REMAJA, LIKE, DAN IDENTITAS: PERSONAL BRANDING DI DUNIA DIGITAL - Sisca Aulia; Keira Djauwvanka Kurniawan; Kathline Alexandra Thedianto (Jurnal Serina Abdimas, 2026)
Personal branding is a strategic process for recognizing, shaping, and conveying a positive and authentic self-image to the social environment. The phenomenon of personal branding among adolescents has experienced significant growth with the increasing use of social media as a space for expression and identity formation. A community service activity conducted at Yakobus High School aimed to analyze how adolescents utilize digital platforms like Instagram, TikTok, and YouTube to build a socially recognized self-image. Through a systematic literature review approach, this activity examines the dynamics between self-presentation, social media algorithms, and the psychosocial impacts that arise from personal branding practices. The results of this activity indicate that adolescents use visual curation strategies, persona consistency, and digital storytelling to gain social validation through metrics such as "likes" and comments. However, intensive engagement with algorithmic logic creates performative pressure, social comparison, and a potential identity authenticity crisis. Furthermore, cultural and gender factors influence how adolescents present themselves in digital spaces. This community service activity emphasizes the importance of digital literacy as an effort to mitigate the psychological and ethical risks that accompany personal branding on social media. Therefore, the integration of digital literacy into educational curricula and more transparent platform policies are strategic steps to support the development of healthy and ethical adolescent identities in the digital era. Personal branding merupakan proses strategis untuk mengenali, membentuk, dan menyampaikan citra diri yang positif dan autentik kepada lingkungan sosial. Fenomena personal branding di kalangan remaja mengalami perkembangan signifikan seiring meningkatnya penggunaan media sosial sebagai ruang ekspresi dan pembentukan identitas. Kegiatan pengabdian yang dilakukan di SMA Yakobus, bertujuan menganalisis bagaimana remaja memanfaatkan platform digital seperti Instagram, TikTok, dan YouTube untuk membangun citra diri yang diakui secara sosial. Melalui pendekatan kajian pustaka sistematis, kegiatan ini menelaah dinamika antara self-presentation, algoritma media sosial, serta dampak psikososial yang muncul dari praktik personal branding. Hasil dari kegiatan ini menunjukkan bahwa remaja menggunakan strategi kurasi visual, konsistensi persona, dan storytelling digital untuk memperoleh validasi sosial melalui metrik seperti “like” dan komentar. Namun, keterlibatan intensif dengan logika algoritma menimbulkan tekanan performatif, perbandingan sosial, dan potensi krisis otentisitas identitas. Selain itu, faktor budaya dan gender berpengaruh terhadap cara remaja menampilkan diri di ruang digital. Kegiatan pengabdian ini menegaskan pentingnya literasi digital sebagai upaya mitigasi terhadap risiko psikologis dan etis yang menyertai personal branding di media sosial. Oleh karena itu, integrasi literasi digital ke dalam kurikulum pendidikan dan kebijakan platform yang lebih transparan menjadi langkah strategis untuk mendukung perkembangan identitas remaja yang sehat dan beretika di era digital.